Radial Forearm Flap for Tongue Reconstruction - Rodney Oliver J. Aragon; Samantha Soriano –Castaneda; Joselito F. David (Philippine Journal of Otolaryngology Head and Neck Surgery, 2008)
Objective: To present a case of tongue reconstruction using radial forearm free flap.